A doctor's memoir of the Romanian Holocaust : survival in Lager Vapniarka and the ghettos of Transnistria - Kessler, Arthur, 1903-2000 1903-2000 (Rochester studies in Central Europe;, 2024)
Based on notes kept while incarcerated in the concentration camps and ghettos of Transnistria, Dr. Kessler's gripping Holocaust memoir tells a story of calculated murder, resistance, and survival.